If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3.26 + -1.7a = 4.7(a + 3.8) Reorder the terms: -3.26 + -1.7a = 4.7(3.8 + a) -3.26 + -1.7a = (3.8 * 4.7 + a * 4.7) -3.26 + -1.7a = (17.86 + 4.7a) Solving -3.26 + -1.7a = 17.86 + 4.7a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4.7a' to each side of the equation. -3.26 + -1.7a + -4.7a = 17.86 + 4.7a + -4.7a Combine like terms: -1.7a + -4.7a = -6.4a -3.26 + -6.4a = 17.86 + 4.7a + -4.7a Combine like terms: 4.7a + -4.7a = 0.0 -3.26 + -6.4a = 17.86 + 0.0 -3.26 + -6.4a = 17.86 Add '3.26' to each side of the equation. -3.26 + 3.26 + -6.4a = 17.86 + 3.26 Combine like terms: -3.26 + 3.26 = 0.00 0.00 + -6.4a = 17.86 + 3.26 -6.4a = 17.86 + 3.26 Combine like terms: 17.86 + 3.26 = 21.12 -6.4a = 21.12 Divide each side by '-6.4'. a = -3.3 Simplifying a = -3.3
| y^1/4/y^1/8 | | 3(t+3.7)=10t-13.4 | | 0=-16t^2-96t | | 1.5(y-7)=0.2-y | | (7v+5)(5v+4)=0 | | 2(x+17)=10x-2 | | Y=1-1.5x | | 2=n-2/7 | | 8+4x=13-1x | | 8x+13-11x=7 | | ×/-5=-8 | | -10y=x^2+8x+4 | | (3n-4)(5n+2)=0 | | y=-x^2+14x-45 | | 5.99+1.99x=20.99 | | 11.3x+7=4.6x+22.41 | | -5.6=y | | (3-i)-(2+6i)= | | 8x+3-7=12 | | Y-1=2(x-3/2) | | 2.6x+78=5.1x+18 | | 7x=9x-9 | | 4+6x=7x-7 | | 5x+9=10x-7 | | 5(x+4)-x=32 | | (4a+3)(a-1)=0 | | 18y=29x-52 | | -16.28=29.3-8.6y | | Y-1=2(x-2/3) | | 3x-(9x+5)=2x-37 | | 8m-20=12+6m | | 8.4y+9.77=-62.47 |